ELM 2016: data update and new functionality of the eukaryotic linear motif resource - Dinkel, Holger; Van Roey, Kim; Michael, Sushama; Kumar, Manjeet; Uyar, Bora; Altenberg, Brigitte; Milchevskaya, Vladislava; Schneider, Melanie; Kühn, Helen; Behrendt, Annika; Dahl, Sophie L.; Damerell, Victoria; et al. (Nucleic acids research, 2016)
Abstract. The Eukaryotic Linear Motif (ELM) resource (http://elm.eu.org) is a manually curated database of short linear motifs (SLiMs). In this update, we pres